Nurses' Attitudes toward Intervening with Smokers: Their Knowledge, Opinion and E-Learning Impact - Králíková, Eva; Felbrová, Vladislava; Kulovaná, Stanislava; Malá, Kateřina; Nohavová, Iveta; Roubíčková, Eva; Pánková, Alexandra; Bialous, Stella A; Wells, Marjorie J; Brook, Jenny; Sarna, Linda (Central European journal of public health, 2016)
BACKGROUND: Numbering about 90,000, nurses represent the largest group of health care providers in the Czech Republic. Therefore, nurses can make a significant impact in the treatment of tobacco dependence, particularly in applying brief interventions to smokers. METHODS: During 2014, 279 nurses from the Czech Republic participated in an e-learning education programme consisting of two Webcasts with additional web-based resources about smoking cessation in relation to health and treatment options in daily clinical practice, particularly regarding brief intervention methods. Before viewing the e-learning programme, and three months after viewing it, the nurses completed a questionnaire documenting their interventions with smokers and their knowledge, attitudes and opinions regarding nurses' roles in smoking cessation. RESULTS: The responses in all of the following categories significantly improved: usually/always asking patients about smoking from 58% to 69% (OR 1.62, CI=1.14-2.29, p=0.007); recommendations to stop smoking from 56% to 66% (OR 1.46, CI=1.03-2.06, p=0.03); assessing willingness to quit from 49% to 63% (OR 1.72, CI=1.23-2.42, p=0.002); assisting with cessation from 21% to 33% (OR 1.85, CI=1.26-2.71, p=0.002); and recommending a smoke-free home from 39% to 58% (OR 2.16, CI=1.54-3.04, p<0.001). The increase in arranging follow-up from 7% to 10% did not constitute a statistically significant improvement, however, this finding is understandable in relation to the status of nurses in the Czech Republic. However, nurses' confidence in helping smokers to quit smoking, their senses of responsibility and determining the appropriateness of these interventions remains inadequate. CONCLUSION: The nurses' brief intervention skills improved significantly after the completion of the e-learning programme, even though reservations remain among this group. The systematic education of nurses aimed at smoking cessation intervention and analyzing their motivation for treatment may contribute to improved nursing care, and thus lead to a reduction of smoking prevalence in the general population.
Keywords: attitude; Attitude of Health Personnel; Česká republika; Computer-Assisted Instruction; nurses; počítačem řízená výuka; mužské pohlaví; smoking cessation; education; Prospective Studies; Adult; postoj zdravotnického personálu; e-learning; Czech Republic; zdravotní sestry; Smoking Cessation; ženské pohlaví; Humans; prospektivní studie; Tobacco Use Disorder; poruchy vyvolané užíváním tabáku; dospělí; Female; Nurses; odvykání kouření; opinion; lidé; Male